THE VALUE AND TOPICALITY OF FEEDBACK IN IMPROVING THE LEARNING PROCESS - Jurs, Pāvels; Špehte, Elita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Feedback delivery is an integral part of the learning process, which provides an effective teaching and learning process. Although students are primarily targeted to get a mark, there are a number of strategies that can be used to maximise students' involvement in the learning process, including providing effective feedback. Purposeful use of feedback through the pedagogical process contributes to a more active involvement of students by developing metacognitive skills (Nicol & Draper 2008). It is important to encourage students, in the learning process and outside it, to ensure reflection on feedback comments and to give preliminary assessment (Taras, 2003). The aim of the article is to update the importance of feedback in the pedagogical process by identifying theoretical regularity in the interpretation of the concept of feedback, as well as undertaking empirical research to clarify students' views on feedback and the effectiveness of its application in the learning process.